ANALISIS TINGKAT PEMAHAMAN DAN KESIAPAN PELAKU UMKM TERHADAP IMPLEMENTASI LAPORAN KEUANGAN BERBASIS SAK EMKM - Linda Francisca Fiani; Sri Opti (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in economic growth and development with the formation of GDP and labor uptake. However, MSMEs have various problems, especially in terms of recording financial statements. The purpose of this study was to determine the effect of the level of understanding and readiness of MSME actors on the implementation of financial statements based on SAK EMKM. This study uses quantitative research with a descriptive approach. The sampling technique used is simple random sampling method. This study processed the primary data obtained using a questionnaire distributed to 100 MSME actors in the Musi Market, Depok City. The tool used to analyze the relationship of variables in this study is Partial Least Square (PLS) version 3.3.3. The results showed that the level of understanding and readiness of MSME actors had a positive and significant effect on the implementation of SAK EMKM-based financial reports. This research is expected to be a reference for accountants associations to conduct socialization and training related to the preparation of financial reports for MSME actors in accordance with SAK EMKM.